2019
DOI: 10.3389/fonc.2019.01403
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Functions and Mechanisms Underlying the Role of METTL3 in Human Cancers

Abstract: Methyltransferase-like 3 (METTL3), a predominantly catalytic enzyme in the N 6 -methyladenosine (m 6 A) methyltransferase system, is dysregulated and plays a dual role (oncogene or tumor suppressor) in different human cancers. The expression and pro-or anticancer role of METTL3 in different cancers remain controversial. METTL3 is implicated in many aspects of tumor progression, including tumorigenesis, proliferation, invasion, migration, cell cycle, differentiation, and viability. Most underlying mechanisms in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
78
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 72 publications
1
78
0
Order By: Relevance
“…The dysregulation of METTL3 has been found to be implicated in many aspects of human cancer cell progression, which has prompted many researchers to explore its possible molecular mechanism. Interestingly, the role of METTL3 in cancer cells is controversial (Zheng et al, 2019), which may be related to the differences in the mechanisms of origin of different cancers. In our study, METTL3 is supposed to exert an oncogenic effect, and knockdown of METTL3 can be efficient in downregulating the global m6A levels for tumor suppression in EEOC.…”
Section: Discussionmentioning
confidence: 99%
“…The dysregulation of METTL3 has been found to be implicated in many aspects of human cancer cell progression, which has prompted many researchers to explore its possible molecular mechanism. Interestingly, the role of METTL3 in cancer cells is controversial (Zheng et al, 2019), which may be related to the differences in the mechanisms of origin of different cancers. In our study, METTL3 is supposed to exert an oncogenic effect, and knockdown of METTL3 can be efficient in downregulating the global m6A levels for tumor suppression in EEOC.…”
Section: Discussionmentioning
confidence: 99%
“…These ndings demonstrated that METTL3 plays different (or even opposite) roles in different cancers [60]. IGF2BP2, a direct target of miR-485-5p, was discovered to be signi cantly up-regulated in the expression of NSCLC, and its depletion signi cantly suppressed tumor cell proliferation and invasion [61].…”
Section: Discussionmentioning
confidence: 98%
“…The key to controlling gene expression at different levels is chemical modi cation of the nucleobases, which can affect the translation of related mRNA, proteins and regulate signal pathways [6]. Among more than 100 RNA chemical modi cations identi ed, N6-methyl-adenosine (m6A) was the most common internal modi cation of mRNA and long non-coding RNA in eukaryotes.…”
Section: Introductionmentioning
confidence: 99%